Adolescent parenthood and HIV-infection in South Africa-Associations with child cognitive development - Kathryn J. Steventon Roberts; Lorraine Sherr; Katharina Haag; Colette Smith; Janina Jochim; Elona Toska; Marguerite Marlow; Lucie Cluver (Public Library of Science (PLoS), 2022)
HIV, both directly and indirectly, impacts child development outcomes. The most severe impacts are for children infected with HIV, and those exposed but uninfected are also shown to have challenges-though less severe. However, little is known regarding the development of children born to adolescent mothers affected by HIV. This study aims to examine cognitive development for children born to adolescent mothers, comparing those children living with HIV, those HIV exposed and uninfected (HEU) and those HIV unexposed (HU). Analyses utilise cross-sectional data from 920 adolescent mother (10-19 years)-first born child dyads residing in the Eastern Cape Province, South Africa. Participants completed detailed study questionnaires inclusive of validated and study specific measures relating to sociodemographic characteristics, HIV, and maternal and child health. Trained assessors administered standardised child development assessments (using the Mullen Scales of Early Learning) with all children. Chi-square tests and ANOVA tests were used to explore maternal and child characteristics according to child HIV status (HIV, HEU, HU) on cognitive development. Linear regression models were used to explore the cross-sectional associations between child HIV status and child cognitive development. 1.2% of children were living with HIV, 20.5% were classified as being HEU and, 78.3% were classified as HU. Overall, children living with HIV were found to perform lower across developmental domains compared to both HEU and HU groups (composite score of early learning: 73.0 vs 91.2 vs. 94.1, respectively: F = 6.45, p = 0.001). HEU children on average scored lower on all developmental domains compared to HU children, reaching significance on the gross motor domain (p<0.05). Exploratory analyses identified maternal education interruption as a potential risk factor for lower child cognitive development scores and, higher maternal age to be protective of child cognitive development scores. These exploratory findings address a critical evidence gap regarding the cognitive development of children born to adolescent mothers affected by HIV in South Africa. Analyses identify stepwise differences in the average scoring on child cognitive development domains according to child HIV status among children born to adolescent mothers affected by HIV; with children living with HIV performing worse overall. Young mothers and their children may benefit from adapted interventions aimed at bolstering child development outcomes. Targeted programming particularly among younger adolescent mothers and those experiencing education interruption may identify those families, particularly in need. Attention to maternal continuity of education and age of conception may be interventions to consider.